Transcriptomic data from panarthropods shed new light on the evolution of insulator binding proteins in insects. (December 2016) - Pauli, Thomas; Vedder, Lucia; Dowling, Daniel; Petersen, Malte; Meusemann, Karen; Donath, Alexander; Peters, Ralph; Podsiadlowski, Lars; Mayer, Christoph; Liu, Shanlin; Zhou, Xin; Heger, Peter; et al.
Abstract Background Body plan development in multi-cellular organisms is largely determined by homeotic genes. Expression of homeotic genes, in turn, is partially regulated by insulator binding proteins (IBPs). While only a few enhancer blocking IBPs have been identified in vertebrates, the common fruit flyDrosophila melanogaster harbors at least twelve different enhancer blocking IBPs. We screened recently compiled insect transcriptomes from the 1KITE project and genomic and transcriptomic data from public databases, aiming to trace the origin of IBPs in insects and other arthropods. Results Our study shows that the last common ancestor of insects (Hexapoda) already possessed a substantial number of IBPs. Specifically, of the known twelve insect IBPs, at least three (i.e., CP190, Su(Hw), and CTCF) already existed prior to the evolution of insects. Furthermore we found GAF orthologs in early branching insect orders, including Zygentoma (silverfish and firebrats) and Diplura (two-pronged bristletails). Mod(mdg4) is most likely a derived feature of Neoptera, while Pita is likely an evolutionary novelty of holometabolous insects. Zw5 appears to be restricted to schizophoran flies, whereas BEAF-32, ZIPIC and the Elba complex, are probably unique to the genusDrosophila . Selection models indicate that insect IBPs evolved under neutral or purifying selection. Conclusions Our results suggest that a substantial number of IBPs either pre-date the evolution of insects or evolved early during insect evolution. This suggests an evolutionary history of insulator binding proteins in insects different to that previously thought. Moreover, our study demonstrates the versatility of the 1KITE transcriptomic data for comparative analyses in insects and other arthropods.